ANALISIS SIYASAH TANFIDZIYAH TERHADAP IMPLEMENTASI PASAL 20 PERATURAN BUPATI NOMOR 14 TAHUN 2023 TENTANG SUSUNAN ORGANISASI DAN TATA KERJA DINAS LINGKUNGAN HIDUP KABUPATEN BENGKULU SELATAN - Irwan Lesmana; Relit Nur Edi; Ahmad Fauzi Furqon (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to analyze the implementation of Article 20 of the Regent Regulation of South Bengkulu Number 14 of 2023 concerning the Organizational Structure and Work Procedures of the Environmental Agency of South Bengkulu Regency in supervising the management of palm oil industrial waste, as well as to analyze it from the perspective of siyasah tanfidziyah. This research uses a qualitative research method with a descriptive approach and is conducted as a case study. Data were collected through interviews, observations, documentation, and literature studies related to environmental supervision and industrial waste management. The results of the study indicate that the Environmental Agency of South Bengkulu Regency has carried out its supervisory functions through environmental quality monitoring activities, field inspections, waste sampling, guidance for business actors, and evaluation of company environmental management reports. However, the implementation of supervision has not been fully optimal because there are still public reports regarding alleged environmental pollution as well as administrative violations committed by several palm oil industrial companies. In addition, there are internal obstacles in the form of limited human resources, budget, and supervisory facilities and infrastructure, while external obstacles are related to the low level of compliance among business actors and the enforcement of sanctions that still tends to be persuasive in nature. From the perspective of siyasah tanfidziyah, the implementation of environmental supervision by the Environmental Agency of South Bengkulu Regency generally reflects the government’s mandate in maintaining public welfare and preventing potential environmental damage. Nevertheless, the implementation still requires strengthening, particularly in terms of law enforcement and follow-up actions against environmental violations, so that the objectives of environmental protection and management can be carried out more effectively in accordance with the principle of maslahah in siyasah tanfidziyah.